Legal Regulation of Cross-Border Digital Business in Southeast Asia in Facing the Expansion of Foreign E-Commerce Platforms - Lenny Mutiara Ambarita; Imelda Mardayanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The development of the digital economy in Southeast Asia is driving the expansion of foreign e-commerce platforms operating across borders and legal jurisdictions. This presents significant opportunities for regional economic growth, but also raises various legal challenges, particularly related to legal certainty, consumer protection, personal data protection, and fair business competition. This study aims to analyze the legal framework for cross-border digital businesses in ASEAN in response to the expansion of foreign e-commerce platforms and to formulate legal strategies that can optimize digital economic growth while protecting the interests of local businesses. This study uses a normative legal research method with a legislative, conceptual, and comparative approach. Data were obtained through a literature review of ASEAN national and regional laws and regulations, international legal instruments, and scientific literature relevant to the topic of cross-border e-commerce. The analysis was conducted qualitatively by examining the suitability and effectiveness of existing legal regulations in responding to the dynamics of the digital economy. The results show that cross-border e-commerce legal regulations in ASEAN are still coordinative and not yet fully harmonized. Differences in national regulations between member countries result in weak consumer protection, legal uncertainty, and challenges in enforcing competition laws against foreign e-commerce platforms with significant market power. Therefore, harmonization of cross-border e-commerce regulations, strengthening digital competition law, and balanced personal data protection are strategic steps that need to be developed at the regional level. This research is expected to provide a conceptual contribution to the development of digital business legal policies in the ASEAN region.